Pengaruh Pemasaran Digital dalam Meningkatkan Brand Awarnness dan Loyalitas Pelanggan pada Produk Kosmetik - Nur Rafidah Karimah; Halimah Zahrah (Indo Publishing, 2026)
This study aims to analyze the influence of digital marketing on brand awareness and its impact on customer loyalty toward Hanasui cosmetic products. A quantitative causal research design was employed using a cross-sectional survey of 210 Hanasui consumers. Data were analyzed using multiple linear regression to examine both direct and indirect relationships among variables. The results indicate that digital marketing has a positive and significant effect on brand awareness. Brand awareness significantly influences customer loyalty. Simultaneously, digital marketing and brand awareness significantly enhance customer loyalty. These findings highlight the strategic role of digital marketing in strengthening brand recognition and building long-term customer relationships in the cosmetic industry.